Notes on reproductive effort parameters and spawning in Chaenocephalus aceratus (pisces, notothenioidei) from the South Shetland Islands - Novillo Estofan, Julio Manuel; Moreira, María Eugenia; Macchi, Gustavo Javier; Barrera Oro, Esteban
The knowledge of the reproductive biology of blackfin icefish Chaenocephalus aceratus in the southern Scotia Arc has been based, primarily on macroscopic observations of its maturation cycle, and lately, on histological analysis of ovaries in developing phase exclusively. Our study on reproduction of C. aceratus collected at Potter Cove (PC), South Shetland Islands (SSI), highlights the importance of histologic techniques to validate gonadal macroscopic maturity stages in order to estimate reliable reproductive parameters, in this work obtained from gravid females. Gonado-somatic index (GSI) of 7-21% (13.50±4.20, n=21), mature oocytes of 2.5-4.0 mm and total fecundity (TF) of 7372-17212 oocytes/female (12,466 ± 2911, n=13) were estimated. Although it is known that variations in the reproductive parameters of C. aceratus between areas of the Scotia Arc are linked to local environmental factors (i.e. hydrographic or biotic), we found close agreement between our results from PC and recent literature data for the South Georgia population, which also arose from the analysis of gravid females. Differently, lower GSIs and oocyte sizes, and higher TF reported lately for the offshore SSI population might be at least partially explained by the fact that these parameters were estimated from the analysis of developing ovaries. Based on our sampling and reproductive effort data, we suggest: (1) the spawning period of C. aceratus at the SSI might be more extended than previously belief, starting from late December until June; (2) the sheltered waters of PC might be a spawning site for C. aceratus, which highlights the role of nearshore areas as spawning grounds of notothenioids. Fil: Novillo Estofan, Julio Manuel. Consejo Nacional de Investigaciones Científicas y Técnicas. Oficina de Coordinación Administrativa Parque Centenario. Museo Argentino de Ciencias Naturales "Bernardino Rivadavia"; Argentina Fil: Moreira, María Eugenia. Ministerio de Relaciones Exteriores, Comercio Interno y Culto. Dirección Nacional del ...